Challenges and Research Progress in Zinc Anode Interfacial Stability - Jing Li; Qianxin Liu; Zixuan Zhou; Yaqi Sun; Xidong Lin; Tao Yang; Funian Mo (Energies)
Aqueous zinc-ion batteries are regarded a promising energy storage system due to their high safety, low cost, high theoretical specific capacity (820 mAh g−1), and low redox potential (−0.76 V). However, in practice, uneven Zn2+ deposition on the surface of the zinc anode can lead to the uncontrolled growth of zinc dendrites, which can puncture the separator and trigger a short-circuit in the cell. In addition, the inherent thermodynamic instability of weakly acidic electrolytes is prone to trigger side reactions like hydrogen evolution reaction and corrosion, further weakening the stability of the zinc anode. These problems not only affect the cycle life of the battery, but also lead to a significant decrease in electrochemical performance. Therefore, how to effectively inhibit the unwanted side reactions and guide the uniform deposition of Zn2+ to suppress the growth of dendrites becomes a key challenge in constructing a stable zinc anode/electrolyte interface. Therefore, this paper systematically combs through the main bottlenecks and root causes that hinder the interfacial stability of zinc anodes at present, and summarizes the existing solutions and the progress made. On this basis, this paper also analyzes the application potential of polymer materials in enhancing the interfacial stability of zinc anodes, which provides new ideas for the direction of subsequent research.